The Specific Types of Female Images in Victorian Novels - Muxammedova Xulkar Eliboyevna (Periodica Journal, 2023)
The following article focuses on the description of women characters in Charles Dickens novels. It is known that the literature of critical Realisms closely connected with the name of Queen Victoria, who governed the country in the XIX century. While developing the gallery of women characters the writer also describes the English culture of that period.
Keywords: characters; description; image; novel